2018
DOI: 10.1136/bjsports-2017-097885
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum physical fitness benefits of recreational football: a systematic review and meta-analysis

Abstract: background A previous meta-analysis showed that maximal oxygen uptake increased by 3.51 mL/ kg/min (95% CI 3.07 to 4.15) during a recreational football programme of 3-6 months in comparison with continuous moderate-intensity running, strength training or a passive control group. In addition, narrative reviews have demonstrated beneficial effects of recreational football on physical fitness and health status. Objective The purpose of this systematic review and meta-analysis was to evaluate the magnitude of effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
107
6
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 53 publications
9
107
6
3
Order By: Relevance
“…Recently, Oliveira et al 14 confirmed that group sports, mainly recreational football, improve body composition, cardiorespiratory fitness, and muscular fitness in overweight and obese children. In this regard, a growing number of systematic reviews and meta-analyses [15][16][17][18] have highlighted the utility of recreational football as a useful form of exercise training because of the intensity elicited [80%-85% of maximal heart rate (HR max )] and movement patterns experienced (~100 high-intensity runs). In turn, it is well established that recreational football induces a range of positive effects on physical fitness including lowering hypertension in middle-aged men and women, improving cardiovascular and metabolic responses in patients with type 2 −1.98, −0.12; P = .031) and the HIIT group (Yo-Yo: 81.2%, ES = 1.03; 95% CI: 0.15, 1.92; P = .025, change-of-direction speed: −5.4%, ES = −0.91; 95% CI: −1.79, −0.04; P = .045).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Oliveira et al 14 confirmed that group sports, mainly recreational football, improve body composition, cardiorespiratory fitness, and muscular fitness in overweight and obese children. In this regard, a growing number of systematic reviews and meta-analyses [15][16][17][18] have highlighted the utility of recreational football as a useful form of exercise training because of the intensity elicited [80%-85% of maximal heart rate (HR max )] and movement patterns experienced (~100 high-intensity runs). In turn, it is well established that recreational football induces a range of positive effects on physical fitness including lowering hypertension in middle-aged men and women, improving cardiovascular and metabolic responses in patients with type 2 −1.98, −0.12; P = .031) and the HIIT group (Yo-Yo: 81.2%, ES = 1.03; 95% CI: 0.15, 1.92; P = .025, change-of-direction speed: −5.4%, ES = −0.91; 95% CI: −1.79, −0.04; P = .045).…”
Section: Introductionmentioning
confidence: 99%
“…physical fitness, running, small-sided games, soccer diabetes, enhancing heart function, increasing physical capacity, improving muscle mass in prostate cancer patients, and increasing bone mineral density and mass. 17 In contrast, only two studies 19,20 have investigated the long-term effects of recreational football on physical fitness in obese boys with the authors concluding recreational football has the potential to prevent and reduce childhood obesity and associated health consequences. Moreover, recreational football has been shown to significantly improve health-related fitness, self-esteem, perceived physical competence, and attraction to physical activity, while PE classes had no effect on these measures.…”
Section: Introductionmentioning
confidence: 99%
“…However, as of the early 2000s investigations into the fitness and health effects of football were initiated. 2 The evidence regarding the application of football as a health-enhancing activity for the general population is currently expanding rapidly with more than 150 scientific articles published over the last 10 years in 35 peer-reviewed international journals, including three metaanalyses, [9][10][11] three narrative reviews, 3-5 three special issues on Football for Health [12][13][14][15][16][17][18][19] and one on football, basketball, team handball, and other team sports. 20 The overall conclusions are summarized in the "Football is Medicine"-model, integrating sports science, sport training physiology, sports medicine, sports psychology and sports sociology results (Figure 1).…”
mentioning
confidence: 99%
“…With regard to research dissemination, there will be a focus on research articles and special issues in high-quality peer-reviewed international journals, like the present issue, with audio-visual coverage of the main results, including these, and with evidencebased popular articles, booklets and books published for the general population as well as healthcare workers and authorities. With regard to implementation there will be emphasis on global dissemination of evidence-based concepts with football training for children (FIT FIRST 7,8 and 11 for Health 6,8 ) and sedentary adults and patient groups (Football Fitness [2][3][4][5][9][10][11][12][13][14][15][16][17][18][19][20][21][22] ), but also evidence-based programmes using, for example, elite football clubs to promote healthy diet and everyday life physical activity for fans (FFIT 23 /EuroFIT 24 ). For such large-scale implementation plans to succeed, a close collaboration is required between important stakeholders in the scientific community, the football governing bodies, the worldwide health organizations and national authorities.…”
mentioning
confidence: 99%
“…Football is the most popular sport worldwide, and participation in football at any level is associated with numerous health benefits 1. However, participation in football at any level incurs a risk of sustaining musculoskeletal injuries 2 3.…”
Section: Introductionmentioning
confidence: 99%